Boundary element analysis of interactions of a bi-material interface crack with inclusions - Niew, Kheng Peng (Nanyang Technological University, 2020)
This project will investigate the interactions between a circular hole/inclusion and an interface crack in a bi-material plate with negligible thickness (plane stress condition) subjected to remote uniaxial tensile stresses. Stresses acting in the perpendicular direction are considered only. An analysis on the stress intensity factors (SIF) at the crack tips is performed using the Boundary Element Method (BEM) in the multi-domain context. Quadratic quarter-point crack tip elements are employed as a solution to stress singularities. It is believed that the interaction can have significant influences on the SIF at the crack tips, with either enhancement or shielding effects. The extent of influence varies depending on parameters such as relative location of the circular hole/inclusion, its geometry and the relative elastic properties of the bi-material plate.